Morphology and molecular phylogeny of a new freshwater ciliate Urosomoida sejongensis n. sp. (Ciliophora, Sporadotrichida, Oxytrichidae) from King George Island, Antarctica - Jung, Jae-Ho; Baek, Ye-Seul; Kim, Sanghee; Choi, Han-Gu (Zootaxa, 2016)
In this study, a new “non-oxytrichid Dorsomarginalia” ciliate, Urosomoida sejongensis n. sp. discovered from freshwater of the King George Island, Antarctica, was investigated using morphological, morphometrical, and molecular methods. Morphology of U. sejongensis is characterized as follows: body shape slender to elongated; cortical granules spherical and colorless, groups of granules formed patchy distribution; ring-shaped structures scattered in cytoplasm; 27–30 adoral membranelles with undulating membranes in Oxytricha pattern; usually 17 frontal-ventral-transverse (FVT) cirri composed of 3 frontal, 1 buccal, 4 frontoventral, 3 postoral ventral, 2 pretransverse ventral and 4 transverse cirri; 1 right and 1 left marginal rows; 3 dorsal kineties with 1 dorsomarginal row, 3 caudal cirri; 1 micronucleus between 2 macronuclear nodules. This new species mainly differs from other congeners by the combination of following morphological features: a micronucleus, cortical granules, and ciliatures (e.g., adoral membranelles, FVT cirri). Urosomoida sejongensis shows a nucleotide similarity of 97.3% with U. agilis, type of this genus, using the SSU rDNA sequence. Molecular phylogeny shows a non-monophyletic relationship among Urosomoida species and emphasizes the need for further morphogenetic studies of this genus and other related species to resolve morphological convergences.